Pressure-induced structural phase transition in the half-Heusler compound CaAuBi - Xie, Lilia S.; Schoop, Leslie M.; Medvedev, Sergey A.; Felser, Claudia; Cava, R. J. (Solid State Sciences, 2014)
We report a structural phase transition of the ternary compound CaAuBi under pressure, from the known cubic half-Heusler phase to a hexagonal LiGaGe type phase, based on synchrotron X-ray diffraction patterns taken under pressures up to 18 GPa. We report lattice parameters and atomic coordinates, and perform total energy calculations for both the cubic and hexagonal phases under different pressures. Finally, we present a structure map that places CaAuBi in the context of related 18 electron XYZ ternary systems. © 2014 Elsevier Masson SAS. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CaAuBi; Half-Heusler; High pressure; X-ray diffraction